Democracy in america eaudiobook - Tocqueville, Alexis de (Recorded Books Inc., 2013)
In 1831, a Frenchman named Alexis de Tocqueville arrived in New York convinced that the democratic spirit America had embraced would eventually spread across Europe. Democracy in America, a treatise on democratic government written from his fresh perspective as an outsider, is now a classic document of political history.